Analysis of Genderlect Style in Pigmalion - Irawati, Tatik (STKIP PGRI Jombang, 2017)
Genderlect styles talk about the style of speech, talk about not what is said but how to express it. Report talk is a term used in assessing male chats that focus on building status. Rapport Talk is a term used to assess women's chats that focus on creating and building relationships. The more specific objectives in this study were to find the differences in communication, communication change and equality of change that backgrounds of women and men in the language used in Pygmalion by Goerge Bernad Shaw. The results of Genderlect style found in pygmalion act 2 category report style found are public speaking, asking question, telling story, listening, and conflict. And in the category of rapport style found is the private speaking, asking questions, conflict, listening, and telling story, while representing the social situation of England in the early 20th century where at that time the style of speaking into a benchmark the social value of British society found Genderlect Style change on Overall figure in Pygmalion Act 2, ie 4 people